Virtual educational ethnography and teacher training (2016)
The paper presents and analyzes a proposal for using virtual educational ethnography in the research of educational phenomena supported by TIC (Information and Communication Technology). The purpose is to describe the methodological strategy for developing the virtual educational ethnography, and assessing its appropriateness in teacher training proceses. The document describes the methodological process, in which participant observation and in depth interview are highlighted; as well as the hermeneutical analysis for unraveling the relationships network and terminology of the phenomena analysed, based on a case study. Subsequently, the article develops a reflection on the importance of this type of educational research in teacher education, with the goal of looking in depth into educational scenarios supported by cyberspace; given that these are the new contexts for creating meaning and giving sense to educational practices as social and cultural ones. Finally, it suggests that the virtual educational ethnography can provide new meaning to pedagogical processes and teacher education programs; in making them, in turn, more in tune with new forms of social and educational life.